2020
DOI: 10.18786/2072-0505-2020-48-022
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic microangiopathy after kidney transplantation: causes, clinical specifics and outcomes

Abstract: Background: Thrombotic microangiopathy (TMA) is a clinical and morphological phenomenon characterized by specific microvascular injury, microangiopathic hemolytic anemia, and damage of various target organs. TMA after kidney transplantation (post-renal transplant TMA) is a serious complication affecting the recipient and graft survival.Aim: To analyze the timing, causes, specifics of the clinical course and outcomes of TMA in renal transplant recipients.Materials and methods: This one-center study was based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…An exhaustive literature search and review (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) regarding the incidence of the lesions of Tx-TMA obtained at the end of R8 revealed that there is a lack of systematic reporting on the incidence of 12 pathological lesions/criteria obtained in the current study. Supplementary Table S3 summarizes the result of the literature review [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Literature Reviewmentioning
confidence: 81%
“…An exhaustive literature search and review (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) regarding the incidence of the lesions of Tx-TMA obtained at the end of R8 revealed that there is a lack of systematic reporting on the incidence of 12 pathological lesions/criteria obtained in the current study. Supplementary Table S3 summarizes the result of the literature review [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Literature Reviewmentioning
confidence: 81%